2022
DOI: 10.3389/fimmu.2022.926740
|View full text |Cite
|
Sign up to set email alerts
|

PRaG Therapy of Refractory Metastatic Gastric Cancer: A Case Report

Abstract: Patients with metastatic gastric cancer had limited treatments and often had a somber prognosis, especially when patients were unable to tolerate high-intensity cytotoxic treatment due to poor physical condition or organ dysfunction after the failure of standard therapy. Here, we reported a metastatic and proficient mismatch repair (pMMR) gastric adenocarcinoma patient with the Eastern Cooperative Oncology Group (ECOG) performance status score of 2 associated with hypoproteinemia and fatigue, and poor appetite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…RC48, a recombinant humanized anti-HER2 antibody conjugated with monomethyl auristatin E, has demonstrated high efficacy in HER2-positive gastric cancer (7). A recent study by Hong Xu et al reported a case of a patient with mediastinal lymph node metastasis who achieved complete remission (CR) following PRaG triple-combination therapy for postoperative gastric cancer (18). This case serves as evidence for the effectiveness of combining anti-PD-1 inhibitor immunotherapy with SBRT, GM-CSF, and RC48 therapy (PRaG3.0, NCT05115500) in HER2-positive refractory multiorgan metastatic gastric cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…RC48, a recombinant humanized anti-HER2 antibody conjugated with monomethyl auristatin E, has demonstrated high efficacy in HER2-positive gastric cancer (7). A recent study by Hong Xu et al reported a case of a patient with mediastinal lymph node metastasis who achieved complete remission (CR) following PRaG triple-combination therapy for postoperative gastric cancer (18). This case serves as evidence for the effectiveness of combining anti-PD-1 inhibitor immunotherapy with SBRT, GM-CSF, and RC48 therapy (PRaG3.0, NCT05115500) in HER2-positive refractory multiorgan metastatic gastric cancer patients.…”
Section: Introductionmentioning
confidence: 99%